Scoring People With Spinal Muscular Atrophy on the Motor Function Measure Using the Microsoft Kinect. Issue 1 (25th October 2022) - Vincent-Genod, Dominique; Rippert, Pascal; Coton, Justine; Le Goff, Laure; Barriere, Aurélie; Berruyer, Anne; Bernard, Marjorie; Garde, Camille; Gutierrez-Garcia, Marta; Gilabert, Stéphanie; Gomes-Lisboade-Souza, Adriana; Daron, Aurore; et al.
Abstract : Purpose: Assess the ability of the Kinect to capture movement and posture of people with spinal muscular atrophy (SMA) during completion of 14 items of the Motor Function Measure, a validated functional rating scale for people with neuromuscular diseases. Methods: Multicenter feasibility study in which Motor Function Measure items were scored as usual by the participant's therapist during the completion (Score-T) while another therapist scored items based only on the visualization of digital data collected using the Kinect (Score-D). Agreement and disagreement were investigated. Results: Twenty people with SMA type 2 or 3 were participants; 142 items were recorded and analyzed. There was 31.7% agreement between Score-T and Score-D for participants with SMA type 2, and 76.2% for those with SMA type 3. Conclusions: The results prevent us from considering the use of Kinect capture to deduce an automated scoring, but this device may be of interest to highlight potential compensations.